Gd Effect on Micro-Crystal Structure and Thermomagnetic Behavior of NiMnSn Magnetic Shape Memory Alloy - Özen, Ecem; Kök, Mediha (My University, 2024)
In this study, the rare earth Gadolinium (Gd) element was added to the NiMnSn alloy, which is an alternative to the NiMnGa alloy group, with the increasing popularity of magnetic shape memory alloys. Since rare earth elements have strategic importance for our country in recent years, Gd element has been preferred in this study. X-rays and SEM-EDX analysis were performed to determine the morphological properties of the crystal structure and microstructure of the alloys. Magnetic measurements of the alloys were made with the physical property measuring device and it was determined that the magnetization values decreased with the addition of Gd.
Keywords: Smart materials; Rare earth element; Gadolinium; Magnetic shape memory alloy